Effect of Digitaria eriantha Endophytic Bacteria on Maize Growth in a Hydroponic System - Johny J. Mendonça; Michelle J. G. Alves; Gisely M. Vitalino; Maria C. S. Barreto; Eric X. Carvalho; José P. Oliveira; Maria L. R. B. Silva; Felipe J. C. Fracetto; Giselle G. M. Fracetto; Mario A Lira Junior (Agronomy)
Brazil is one of the largest grain producers worldwide, with yields heavily dependent on ecologically and financially expensive inputs. One possible approach to reduce these inputs is inoculation with plant-growth-promoting bacteria, whose large-scale use depends on a continual search for new genotypes for inoculant production. Several bacteria with potential for this have been isolated from plants that are more adapted to stressful environments. Thus, we aimed to evaluate the potential of pangolão grass (Digitaria eriantha cv. Suvernola) endophytic bacteria both in vitro and on maize growth. To this end, endophytic bacteria were isolated from pangolão grass of a tropical semiarid climate and a random subset of 80 strains was evaluated for biological nitrogen fixation, HCN, IAA and siderophore production and calcium phosphate solubilization, and later for maize growth promotion. All strains were positive for at least one of these in vitro growth promotion mechanisms and some strains increased maize plant height and root length, including some with better results than plants receiving commercial inoculants, confirming the potential of endophytic bacteria from stress-adapted plants. In vitro results had poor correlation with plant growth promotion, which indicates that the common practice of using these laboratory techniques as a pre-selection tool before a subset of strains is evaluated for plant growth promotion might result in the rejection of potentially interesting strains.